Do some prefer to pay? Identifying bias against free COVID-19 tests - Yeonsoo Baik; Cedric H. Bien-Gund; Gregory P. Bisson; Robert Gross; Jessica Fishman (Elsevier, 2024)
Objectives: In the United States, a federal emergency program has made SARS-CoV-2 self-test kits available at no cost. It is unclear how widely free tests are preferred. We conducted a survey to estimate the proportion of respondents who do not prefer a free test. We hypothesized that free tests would not be preferred universally, and that a preference for paying would be more common among those with conservative politics than with liberal politics, regardless of income. Design: Observational study design. Methods: A national sample of US adults completed an online survey. To reduce potential enrollment bias, the survey's focus was not specified beforehand. To prioritize a high-risk group, participation was limited to those who were unvaccinated or were incompletely vaccinated in the primary series against COVID-19. Participants reported their testing preferences and socio-demographic characteristics, including political affiliation. The main outcome assessed if a participant preferred to pay for a self-test or receive a free one (subsidized by the US government). Results: Among 1215 participants, (73%, n = 886) preferred free self-testing, while 27% (n = 329) preferred to pay for the same testing. After adjusting for income, the odds of preferring to pay for self-testing were 66% higher in "strong" Republicans compared to "strong" Democrats (odds ratio = 1.66, 95% confidence interval = 1.07-2.62). Conclusions: More than a quarter of individuals preferred paying for these tests. This preference was more likely among those with right-wing politics. Policy implications are discussed, along with future research directions.